Pengaruh Media Papan Flanel Berbasis Metode SAS (Struktural Analitik Sintetik) terhadap Keterampilan Membaca Permulaan Peserta Didik Kelas II SDN 15 Mataram - Riha Safitri; Moh. Irawan Zain; Heri Setiawan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Early reading skills are fundamental abilities that students must master. In practice, some students still experience difficulties in developing these skills. The purpose of this study is to examine the influence of flannel board media based on the SAS (Structural Analytic Synthetic) method on the early reading skills of second-grade students at SDN 15 Mataram. The research employed a quasi-experimental design with a non-equivalent control group. The population consisted of all second-grade students at SDN 15 Mataram, totaling 53 students. Saturated sampling was used, resulting in class IIB as the experimental group and class IIA as the control group. The experimental group received treatment using flannel board media based on the SAS method, while the control group was taught through conventional methods. Data collection instruments included tests and observation sheets, with data gathered through performance tests and observations. The independent variable (X) in this study was the flannel board media based on the SAS (Structural Analytic Synthetic) method, while the dependent variable (Y) was the early reading skills of second-grade students at SDN 15 Mataram. Based on the hypothesis test results, the significance value (2-tailed) was 0,013 < 0,05. This indicates that, according to the independent sample t-test, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. In other words, there is a significant difference in the mean early reading skills between the experimental class taught using the SAS-based flannel board media and the control class taught with traditional methods. Therefore, it can be concluded that the SAS-based flannel board media has a significant effect on the early reading skills of second-grade students at SDN 15 Mataram.